NUCLEAR WEAPONS – RISKS IN CASE OF THEIR POTENTIAL USE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The aim of the research is to evaluate nuclear weapons risks in the case of their potential use. It is known that the properties of a particular radioactive isotope do not depend on the method of its formation, since no fundamental boundary can be drawn between natural and artificial radioactive substances. From a biological point of view, two types of radioactive substances are distinguished. If people have been in contact with natural radioactive substances since their existence, then artificial radioactive substances first appeared in the biosphere in 1945, immediately after the first nuclear weapons tests, in particularly after their use over the Japanese cities of Hiroshima and Nagasaki.A nuclear explosion differs from an explosion of ammunition loaded with conventional explosives, where almost all the energy is released as kinetic (thermal) energy, and the destructive effect is mainly concentrated in the blast (shock wave). The strong electromagnetic field (EMF) can induce electric current in antennas, cables, power lines and sensitive electrical and radio equipment. As a result, cables and wires can melt, equipment can burn out and insulation can be damaged. The radius of destructive effect of EMP depends on the type of explosion and the power of the nuclear weapon. According to American experts, the radius of destructive effect of a low-altitude air explosion with a power of 1 Mt is 32 km; for 10 Mt it is 115 km; and for 50 Mt it is 190 km. Long-lived radioisotopes also include cesium-137, cesium-144, ruthenium-106, zirconium-95, etc. The main contamination threat to plants and plant products is strontium-90. The destructive effect of a shock wave on people, animals, plants and objects is determined by the overpressure in kilograms per square centimeter and the duration of the shock wave. The overpressure varies depending on the distance from the center of the explosion.